The Influence of Motivation, Discipline, and Work Environment on the Performance of Teachers at SMP N 1 Wewewa Timur - Deke, Oktavianus; Kaleka, Yohanis Umbu; Aryani, Ni Wayan Prawita; Wadu, Welhem Mine; Lede, Yulita Adelfin; Engge, Yohanes; Dappa, Jumiati (Sean Institute, 2025)
This study aims to analyze the influence of work motivation, work discipline, and work environment on teacher performance at SMP Negeri 1 Wewewa Barat. Teacher performance is widely recognized as a key determinant of educational quality and student achievement. It is shaped by various internal and external factors, including psychological, behavioral, and organizational aspects. To examine the complex relationship among these factors, a quantitative approach was employed using path analysis, allowing for both direct and indirect effect testing. Data were collected through structured questionnaires distributed to all teachers at the school, making it a population study with 20 respondents. The findings from the F-test reveal that work motivation (X₁), work discipline (X₂), and work environment (X₃) collectively exert a significant influence on teacher performance (F = 18.761; sig. = 0.000). However, results from the partial test (t-test) show that only work motivation has a statistically significant individual impact (t = 7.468; sig. = 0.000), while the other two variables do not. Following model trimming to refine the regression equation, the final model retained only work motivation as a significant predictor, resulting in a coefficient of determination (R²) of 0.756. These results highlight the central role of motivation in shaping teacher performance, with 75.6% of performance variability explained by motivational factors alone. Therefore, educational stakeholders are encouraged to prioritize policies and practices that cultivate intrinsic motivation among teachers, such as recognition systems, professional development, and supportive school cultures. The study provides valuable implications for improving educational outcomes through evidence-based teacher management strategies